(untitled) (Revista Brasileira Multidisciplinar, 2022)
The present study proposes to verify which factors inherent to the organizational and operational structure of the executing agents of the Food Acquisition Program-PAA, at the local level, that most influence their performance, reporting how the program is operationalized and the organizational structure present in the Purchase with Simultaneous Donation – CDS modality, based on the role played by the Food Bank in the municipalities of Araraquara/SP and São Carlos/SP. For this, case studies were used as a methodological strategy, based on the application of two methods: documentary research and interviews with the managers of the Food Bank in the two municipalities and with the manager of CRAS in the municipality of Araraquara/SP. Among the results, it is possible to highlight that the design of the organizational structure of the PAA, in both municipalities, demonstrated the central role played by the Food Bank for the performance of the program. And that this Bank, at the municipal level, should be treated as an intermediary unit rather than a receiving unit. It also indicated that, although the PAA was designed to be developed and implemented by all Brazilian municipalities, the execution only via CONAB proved to be very superficial and better executed when worked in conjunction with the existing structure for the Municipal PAA.